Potable water quality issues in Upper Egypt: a comparative qualitative study on drinking water quality in the rural villages of Minya, Upper Egypt - Alia, Tamer (AUC Knowledge Fountain, 2019)
Water is life and Egypt faces an ongoing problem of unsafe water quality. People, especially in rural areas, are becoming ill and might not even be aware it is partially due unclean water they are consuming. This is a qualitative study that, from both social and public health lenses, aims at comparing the perception of families in Egyptian villages (end users) towards the water they are receiving in their homes with the situation as described (and seen by the author) by the service provider (government) within the entire process of clean water provision. In-depth interviews were conducted with families from three villages in Upper Egypt, government employees and a project manager from a non-profit organization that has carried out water projects with the government. Additionally, four samples of water were taken from the villages and tested to compare results with international standards. The analysis of the data is divided into themes under the main sections of end users and service provider. Findings reveal the reality of contaminated water despite the presence of water treatment stations. Further investigation is needed into the effectiveness of water treatment stations and into new low-tech solutions to ensure the safety of drinking water provision.